Regulatory compliance and environmental sustainability practices of manufacturing entrepreneurial ventures in Uganda - Sendawula, Kasimu; Turyakira, Peter; Mbidde Ikiror, Cathy (Asia Pacific Journal of Innovation and Entrepreneurship, 2021)
The purpose of this paper is to establish whether all the dimensions of regulatory compliance matter for environmental sustainability practices of manufacturing small and medium entrepreneurial ventures (SMEVs) using evidence from Uganda. Design/methodology/approach – This study is cross-sectional and correlational. Data was collected through a questionnaire survey of 106 manufacturing SMEVs. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 23. Findings – The results indicate that controls, legitimacy and deterrence do matter for environmental sustainability practices of the manufacturing SMEVs in Uganda, unlike social norms and values. Originality/value – This study fosters the understanding of environmental sustainability practices, as it provides insights on whether all the dimensions of regulatory compliance do matter for environmental sustainability practices of manufacturing SMEVs in Uganda.
Keywords: Environmental sustainability practices; Regulatory compliance; Social norms and values; Controls, Legitimacy; Deterrence